Microwave-enhanced electroanalytical processes: generator-collector voltammetry at paired gold electrode junctions. - Rassaei, L; French, R; Compton, R; Marken, F (2009)
Generator-collector electrode systems allow redox processes and reaction intermediates from multi-step electrode reactions to be monitored. Analytically, collector electrode current responses are insightful and highly sensitive due to (i) the absence of capacitive current components and (ii) an enhanced current response due to 'feedback' between generator and collector electrode. Here, a symmetric gold-gold junction grown by controlled electro-deposition is employed for generator-collector voltammetry in conjunction with microwave activation. Three redox systems are investigated in aqueous 0.1 M KOH: (i) the reduction of Fe(CN)(6)(3)(-), (ii) the reduction of chloramphenicol, and (iii) the reduction of oxygen. Microwave radiation, when focused into the electrode-solution interfacial zone, causes locally enhanced temperatures with electrode surface temperatures reaching up to typically 380 K (estimated from the shift in the Fe(CN)(6)(3)(-/4)(-) equilibrium potential, at both gold electrodes). The resulting increase in the rate of diffusion and the onset of convection result in non-linear Arrhenius limiting current characteristics and in an increase in collection efficiency with microwave power. The gold electrode junction geometry allows diffusion effects (which increase the feedback current within the gap) to dominate over convection effects (which suppress the feedback current).